Medicinal plants of Otwal and Ngai Sub Counties in Oyam District, Northern Uganda - Acipa Annabel; Kamatenesi Maud M; Oryem-Origa Hannington (BMC, 2011)
Abstract Background An ethnobotanical study was carried out in four parishes in the Ngai and Otwal Sub Counties in Oyam district, Northern Uganda, where insurgency has been prevalent for the past 20 years. Documenting medicinal plant species used in treating various health conditions among the local people. Methods Information was obtained from mainly the local population, the traditional healers and other experienced persons through interviews, formal and informal discussions and field excursions. Results Seventy one plant species were reported for use in the treatment of various diseases in the study area. These plant species belongs to 41 families, with Asteraceae being the most represented. Roots were ranked the commonest plant part used. Oral administration was the most frequently used route of administration. A total of 41 different health conditions were reported to be treated by use of medicinal plant species. Thirty nine percent of the recorded plant species were reported for treating stomach related ailments. Conclusion The use of medicinal plants in primary healthcare is still a common practice in Ngai and Otwal Sub Counties. The trust they have is built on the curative outcome properties claimed, poverty and armed conflict that lead to inadequate healthcare facilities. The generation gap caused by the over 20 years of insurgency in the area has brought about knowledge gap on the usage of medicinal plant species between the young and the older generation.